ANALISIS KESULITAN BELAJAR MATEMATIKA SISWA DITINJAU DARI KEMAMPUAN KONEKSI MATEMATIKA - Laili, Fitri Jannatul; Puspasari, Ratih (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2018)
This study aims to discribe what are the difficulties of learning mathematics experienced which students in terms of mathematical connections ability class VIII MTs. darul Falah Bendiljati. This research is a descriptive qualitative research using test and interview method. Research subjects randomly selected as many as 30 students from two classes. The results showed that each student has difficulty learning mathematics in terms of mathematical connection capabilities are: (1) Less understanding of mathematical concepts that have been studied; (2) Not connecting mathematical concepts to be studied with previously known concepts; (3) Quicly forgot a mathematical concept he did not understand; (4) The habit of learning by understanding the concept, so when given a slightly different matter the students find it difficult; (5) Consider mathematics as a science that interconnects one and other concepts seperately; (6) Less aware of the benefits of consepts in mathematics to support and improve his ability in other fields of science; (7) Understanding concepts  that are not applied directly to life, so the concept of mathematics is a concept in a mathematics only and not used or in connect with daily life. Keywords: difficulty learning, mathematics connection abilityAnandita, Gustine. P. 2015. Analisis Kemampuan Koneksi Matematis siswa SMP Kelas VIII pada Materi Kubus dan Balok. Skripsi tidak dipublikasikan. Semarang: Uiversitas Negeri Semarang.NCTM. 2000. Principles and standars for school mathematics. USA : The National Council of Teachers of Mathematics, Inc.Poespoprodjo. 1999. Logika Ilmu Menalar. Bandung: Pustaka Grafika.Kuswana, Wowo Sunaryo. 2011. Taksonomi Berpikir. Bandung: PT. Remaja Rosdakarya.Suherman, H.L.E., et al. 2003. Strategi pembelajaran matematika kontemporer (Rev.ed.).Bandung: JICA Universitas Pendidikan Indonesia. Septiati, E. 2012. Kefektifan pendekatan konstruktivisme terhadap kemampuan koneksimatematis mahasiswa pada mata kuliah analisis real I, (Online), http://eprints.uny.ac.id/id/eprint/7568, diakses tgl 09 Februari 2017.Sugiman. 2008.  Koneksi Matematika Dalam Pembelajaran Matematika di Sekolah Menengah Pertama. (Online). Jounal.uny.ac.id. diakses 15 Mei 2017.Yuniawatika. 2011. Penerapan pembelajaran matematika dengan strategi REACT untuk meningkatkan kemampuan koneksi dan representasi matematika siswa sekolah dasar [Versi electronik].Edisi Khusus, 2, 107-120